1988
DOI: 10.1095/biolreprod39.4.901
|View full text |Cite
|
Sign up to set email alerts
|

Tissue and Cell Specificity of Immobilin Biosynthesis1

Abstract: The mechanisms for the initiation of sperm motility have been poorly understood until recently. Immobilin is a novel mucin glycoprotein of high molecular weight found in the cauda epididymis of the rat that, at concentrations equivalent to those found in native cauda epididymal fluid, reversibly inhibits sperm motility. In this study, immobilin was purified from rat cauda epididymal fluid to apparent homogeneity and used to generate polyclonal antibody in rabbits. The antibody was characterized by immunoblotti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…In the corpus and cauda regions, principal cells were unreactive. These observations extended the preliminary results obtained by Ruiz-Bravo (1988).…”
Section: Introductionsupporting
confidence: 91%
“…In the corpus and cauda regions, principal cells were unreactive. These observations extended the preliminary results obtained by Ruiz-Bravo (1988).…”
Section: Introductionsupporting
confidence: 91%
“…The present study extends the light microscope immunofluorescent findings of Ruiz-Bravo (1988) on the localization of immobilin to a more complete analysis of all regions of the extratesticular duct system. Using light and electron microscope immunocytochemistry we have investigated the role the different epithelial cells play with respect to immobilin.…”
Section: Discussionsupporting
confidence: 59%
“…Efferent duct ligation and unilateral orchidectomy both result in a dramatic decrease in epididymal Sa-reductase activity, especially in the proximal portion of the tissue (Robaire et al, 1977;Robaire, 1979). Thus, in the initial segment, epididymal Sa-reductase activity is regulated in a paracrine manner by a substance directly entering the epididymis via the efferent ducts, and not via the general circulation ; this type of regulation has also been noted for immobilin (Ruiz-Bravo, 1988), CRES (Cornwall et al, 1992), and gamma-glutamyl transpeptidase (Palladino and Hinton, 1994) and has been termed as "lumincrine" by Hinton's group . Based on the results of a series of endocrine manipulations that altered the nature of the substance( s) entering the epididymis from the testis via the efferent ducts Robaire and Zirkin, 1981;Robaire and Viger, 199S), it can be shown that the paracrine factor regulating nuclear epididymal Sa-reductase activity is of Sertoli cell origin and under the control of testosterone.…”
Section: Regulation Of Epididymal Sa-reductasesmentioning
confidence: 73%
“…A characteristic checkerboard-like pattern can be seen for epididymal principal cells after immunolocalization of a number of gene products such as immobilin (Ruiz-Bravo, 1988, Hermo et a!., 1992b, clusterin (SGP-2, Hermo et a!., 1991), and mouse epididymal protein 9 (Rankin et a!., 1992). Normally, either at the point in the duct where immunostaining first appears or when the signal stops being expressed there are, in a given cross section, some cells that are intensely stained while others remain unreactive.…”
Section: Epithelial Proteinsmentioning
confidence: 99%